The Aqedah (Genesis 22), God’s Promise, and Its Relation to the Post-Pandemic Churches - Yong, Steven (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2023)
Gerhard von Rad’s exegesis on Genesis 22 shows that the test of Abraham or the Aqedah contains a problem of the endangered promise. Isaac was seen as the promised child, the proto-Israel. Hence, there is a dilemma of the endangered people of God if Isaac is sacrificed. So too the church, along with the entire history of salvation, would not exist. Abraham’s experience can serve as a blueprint of how God deals with his church, the Israel of God. It is normal then to ask the follow-ing: How does God deal with his church? Can the church continue to thrive in this post-pandemic era? This paper aims to provide some answers by showing, first of all, that Genesis 22 is a culmination test from the initial calling to Abraham in Genesis 12. This command and the related verbs are then examined in the context of Abraham’s calling from Genesis 12 until the test in Genesis 22. Finally, some spiritual implications and insights are drawn to encourage post-pandemic churches as they journey on with the Lord. As the world grapples with the profound impact of the global health crisis, it is argued that Genesis 22 is not just a problem of an endangered promise, but rather a complex relationship Abraham has between a divine promise that is also entangled with and should be understood in relation to, a divine command, a doubtful and responding faith, and an act of obedience and disobedience. In short, faith indeed is a pilgrimage.